STRATEGI GURU PAI DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SD NEGERI DANARAJA 02 - Septyana Suryani; Koko Khoerudin (CV. Lafadz Jaya, 2026)
This research is motivated by the importance of appropriate learning strategies for lower-grade students who possess specific cognitive and emotional developmental characteristics, such as short attention spans and a tendency to get bored easily. The purpose of this study is to describe in depth the strategies used by Islamic Religious Education (PAI) teachers to increase the learning interest of third-grade students at SD Negeri Danaraja 02, Tegal. This study employs a descriptive qualitative method, with data collection techniques including observation, structured interviews, and documentation. Data analysis was conducted through reduction, data display, and conclusion drawing, using triangulation techniques to ensure data validity. The results show that students' interest in learning is heavily influenced by the teacher's delivery method. Varied learning strategies, such as practice-based learning (wudu and prayer), the use of songs, visual media, and contextual approaches, proved effective in increasing student engagement and understanding compared to pure lecture methods. Although efforts have been made to implement the principles of the Merdeka Curriculum, teachers still face challenges due to the diverse abilities of students. The conclusion of this study is that the use of active, creative, and fun learning strategies tailored to the concrete operational stage of children can significantly increase students' interest in PAI subjects. It is suggested that PAI teachers continue to develop adaptive pedagogical methods to accommodate student diversity and optimize learning outcomes.